The cracked tooth syndrome--crown root vertical fracture - Majid, Z.A.; Zain, R.B. (1988)
A case of an incomplete tooth fracture followed by a complete fracture was presented. The difficulty of diagnosing this condition was discussed as well as the possible histological explanation of the symptoms experienced by the patient. It once again points out to practising dentists, that whilst deep pockets can give rise to severe periodontal pain, intense and excruciating pain should be investigated with the cracked tooth in mind.